The C677T methylenetetrahydrofolate reductase variant and third trimester obstetrical complications in women with unexplained elevations of maternal serum alpha-fetoprotein - Greenberg Cheryl R; Evans Jane A; Björklund Natalie K; Seargeant Lorne E; Schneider Carol E; Chodirker Bernard N (BMC, 2004)
Abstract Introduction The C677T MTHFR variant has been associated with the same third trimester pregnancy complications as seen in women who have elevations of maternal serum α-fetoprotein (MSAFP). We hypothesized that these women with third trimester pregnancy complications and MSAFP elevations would have an increased frequency of the variant compared to an abnormal study control group (women with MSAFP elevations without pregnancy complications) as well as to normal population controls. Methods Women who had unexplained elevations of MSAFP in pregnancy were ascertained retrospectively. The frequency of the C677T MTHFR variant among those women with unexplained elevations of MSAFP who had experienced later pregnancy complications was compared to that of women with unexplained elevations of MSAFP without complications as well as to that of the previously established Manitoba frequency. Results Women who had complications of pregnancy and an unexplained MSAFP elevation had a higher allele frequency for the C677T MTHFR variant (q = 0.36,) compared to women with MSAFP elevations and normal pregnancy outcomes (q = 0.25, OR 1.73 95% CI 1.25-2.37, p = 0.03). The frequency was also higher than that of the population controls (q= 0.25, OR 1.70 95% CI 1.11-2.60, p = 0.007). The frequency in women with MSAFP elevations without pregnancy complications was not significantly different from that of the population controls (p = 0.41). Conclusion Women with unexplained elevations of MSAFP and who experience complications in later pregnancy are more likely to have one or two alleles of the C677T MTHFR variant.